PSYCHOLOGY OF ADVERTISING AND ITS INFLUENCE ON CONSUMER PURCHASING BEHAVIOR - Erkinov Shahzod Bakhodir o’gli (Galaxy International Interdisciplinary Research Journal, 2022)
Today's market is filled with a huge number of products that satisfy the same needs; most products are identical, and new products are easily copied by competitors. In such conditions, the main value of any company, the main factor that "sells" a product, is the relationship with consumers. It is the consumer who is the only subject of the internal, macro - and microenvironment of the company, which gives it his money. Consequently, if the relationship with the consumer is built, then the flow of funds in the form of turnover and profit is ensured.Studying the psychological influence of advertising on a person, researching the influence of an advertiser on a consumer, it is necessary to understand that the effectiveness of such influence cannot be determined by some individual mental processes, psyche characteristics or characteristics of the advertisement itself, or only by its memorability, ability to attract attention or evoke positive emotions. To understand where to look for reserves for increasing the effectiveness of advertising on the consumer and what mistakes were made, it is necessary to study in detail practically the entire psyche of the consumer, all his mental processes.